A 3 DOF Model for an Electromagnetic Air Mount. (18th January 2012) - Kim, HyungTae; Kim, CheolHo; Kang, SungBok; Lee, KangWon; Baek, JaeHo; Han, HyunHee
Abstract : A 4 × 4 matrix model with three degrees of freedom is proposed as a means for controlling microvibrations and applied to an electromagnetic isolator. The model was derived from an assumption based on small- and low-frequency vibrations. The coordinates of the 3 DOF was composed of the 4 variables, representing a vertical position, pitch, roll, and a proof term. The coordinates were calculated from the 4 position sensors in the isolator and formulated into a 4 × 4 matrix, which possesses inversive full rank. The electro-magnetic isolator was built for a simulated machine in semiconductor manufacturing and consisted of a heavy surface plate, sensors, amps, a controller, and air springs with electromagnets. The electromagnets are installed in a pneumatic chamber of the individual air spring. The performance of the 3 DOF model was experimented and compared with that of a 1 DOF model in an impact test. The settling time in the result was reduced to 25%.